ISG15 promotes M5-induced hacat cell proliferation through Wnt signaling in psoriasis - Sun Xianqi; Li Yuzhen; Yu Huiwen; Lin Jiaying; Wang Chen; Liu Quanlin; Bai Bingxue (Frigid Zone Medicine)
Psoriasis is a common chronic, recurrent, immune-mediated inflammatory skin disease, which tends to occur in cold areas. Its pathogenesis is currently unclear. This study aims to screen differentially expressed genes in the psoriasis dataset, identify the central genes, detect the expression of central genes in psoriasis lesions of patients in the cold regions and then conduct further research.